Extraversion, neuroticism, attachment style and fear of missing out as predictors of social media use and addiction - Blackwell, David; Leaman, Carrie; Tramposch, Rose; Osborne, Ciera; Liss, Miriam (Personality and individual differences, 2017)
Social media use is prevalent in today's society and has contributed to problems with social media addiction. The goal of the study was to investigate whether extraversion, neuroticism, attachment style, and fear of missing out (FOMO) were predictors of social media use and addiction. Participants in the study (N=207) volunteered to complete a brief survey measuring levels of extraversion, neuroticism, attachment styles, and FOMO. In the final model of a hierarchical regression, younger age, neuroticism, and fear of missing out predicted social media use. Only fear of missing out predicted social media addiction. Attachment anxiety and avoidance predicted social media addiction, but this relationship was no longer significant after the addition of FOMO. •Fear of missing out predicted social media use and addiction.•Anxious and avoidant attachment predicted social media addiction.•Extraversion and Neuroticism predicted social media use.